Corporate social responsibility in the corporate reputation of mining companies in Tacna, PERU - Aguilar Condori, Ines Maritza (2025)
The objective of the study was to analyze corporate social responsibility (CSR) in the corporate reputation of mining companies in Tacna, Peru. The study was conducted between June and November 2024 in Tacna, Peru. A sample of 343 individuals from Palca and Ilabaya was used to evaluate the relationship between CSR and corporate reputation of mining companies. Validated questionnaires were employed, and Cronbach's alpha coefficient was 0.93. Descriptive statistics were used to analyze the variables through relative percentages, and their association was tested using the non-parametric Spearman’s Rho test. The results were considered significant when p<0.05. The findings revealed a negative assessment in the social (91.5% low), economic (85.1% low), and environmental (80.2% low) dimensions. These data suggest a disconnect between mining companies and local communities. The perception of corporate reputation was also negative, with 79% rating ethical values as low, 78.4% evaluating labor conditions negatively, and 80.2% perceiving weak reputational management. The Spearman’s Rho correlation (0.748) shows a significant relationship between CSR and corporate reputation, highlighting the importance of strengthening CSR practices to improve reputation. The conclusion is that the negative perception of CSR practices reflects a disconnect and lack of transparency. It is crucial to align policies with local expectations, improve communication, and ensure consistency to strengthen corporate reputation.